Oestrogens and Progestagens: Synthesis and Action in the Brain. (July 2016) - Rossetti, M. F.; Cambiasso, M. J.; Holschbach, M. A.; Cabrera, R.
Abstract : When steroids, such as pregnenolone, progesterone and oestrogen, are synthesised de novo in neural tissues, they are more specifically referred to as neurosteroids. These neurosteroids bind specific receptors to promote essential brain functions. Pregnenolone supports cognition and protects mouse hippocampal cells against glutamate and amyloid peptide‐induced cell death. Progesterone promotes myelination, spinogenesis, synaptogenesis, neuronal survival and dendritic growth. Allopregnanolone increases hippocampal neurogenesis, neuronal survival and cognitive functions. Oestrogens, such as oestradiol, regulate synaptic plasticity, reproductive behaviour, aggressive behaviour and learning. In addition, neurosteroids are neuroprotective in animal models of Alzheimer's disease, Parkinson's disease, brain injury and ageing. Using in situ hybridisation and/or immunohistochemistry, steroidogenic enzymes, including cytochrome P450 side‐chain cleavage, 3β‐hydroxysteroid dehydrogenase/Δ5‐Δ4 isomerase, cytochrome P450arom, steroid 5α‐reductase and 3α‐hydroxysteroid dehydrogenase, have been detected in numerous brain regions, including the hippocampus, hypothalamus and cerebral cortex. In the present review, we summarise some of the studies related to the synthesis and function of oestrogens and progestagens in the central nervous system.